2016
DOI: 10.1103/physreva.94.063812
|View full text |Cite
|
Sign up to set email alerts
|

Phase-space views into dye-microcavity thermalized and condensed photons

Abstract: We have observed momentum-and position-resolved spectra and images of the photoluminescence from thermalised and condensed dye-microcavity photons. The spectra yield the dispersion relation and the potential energy landscape for the photons. From this dispersion relation, we find that the effective mass is that of a free photon not a polariton. We place an upper bound on the dimensionless two-dimensional interaction strength ofg 10 −3 , which is compatible with existing estimates. Both photon-photon and photon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
5
14
1
Order By: Relevance
“…[12] Theoretical calculations from the correlation data [13] and the master-equation model [14] provide rather low estimates for the dimensionless 2D interaction parameter [15]g ≈ 10 −7 − 10 −4 . Experimentally, the thermo-optic part of interaction proves to be dominant, with g ≈ 10 −4 , [2,16] while the Kerr non-linearity may arguably be enhanced by adding suitable materials to the dye solution. It is important to note that whereas the Kerr component of interaction is local and fast (happening on the timescales of spontaneous emission of the dye ≈ 1 ns), the thermo-optic part can be tuned by Figure 1.…”
Section: Doi: 101002/andp201800431mentioning
confidence: 98%
“…[12] Theoretical calculations from the correlation data [13] and the master-equation model [14] provide rather low estimates for the dimensionless 2D interaction parameter [15]g ≈ 10 −7 − 10 −4 . Experimentally, the thermo-optic part of interaction proves to be dominant, with g ≈ 10 −4 , [2,16] while the Kerr non-linearity may arguably be enhanced by adding suitable materials to the dye solution. It is important to note that whereas the Kerr component of interaction is local and fast (happening on the timescales of spontaneous emission of the dye ≈ 1 ns), the thermo-optic part can be tuned by Figure 1.…”
Section: Doi: 101002/andp201800431mentioning
confidence: 98%
“…The small mode volume of the system allows self‐diffusion that quickly circulates photobleached dye molecules out of the cavity mode, in which the authors demonstrated CW operation of a dye laser without externally driven recirculation, with single mode tunability over a bandwidth of 20 nm. In parallel with dye‐based microlasers, dye molecules incorporated in cavities were also investigated for photon condensations, wherein the photons can reach thermal equilibrium through frequent energy exchanges with the thermal bath of dye–solvent vibrations . Walker et al.…”
Section: Exciton‐polaritons In Open‐access Microcavitiesmentioning
confidence: 99%
“…In parallel with dye-based microlasers, dye molecules incorporated in cavities were also investigated for photon condensations, wherein the photons can reach thermal equilibrium through frequent energy exchanges with the thermal bath of dye-solvent vibrations. [128][129][130][131][132] Walker et al reported nonequilibrium BEC of a very small number (7 ± 2) of photons in the chip-based open-access microcavity incorporating dye molecules. [133] The concave mirror, with a RoC of 400 µm fabricated by FIB milling, was specifically designed to form a photonic potential of 2D harmonic oscillator that enabled the observation of a multimode condensate regime of photons that exhibit strong intermode correlations.…”
Section: Dye Lasers and Photon Condensationsmentioning
confidence: 99%
“…Note that, as mentioned in the introduction, the thermo-optical effect dominates the photon-photon interaction. Therefore, this value cannot be directly compared with the measured values [5,62,65], since we only model one of the respective contributions. Now we investigate how g  depends on the parameters of our model.…”
Section: Photon-photon Interaction Strengthmentioning
confidence: 99%